The impact of construction on the environment - the European experience of normative and legal regulation in Ukraine - Skakun, V.А. (Ways to Improve Construction Efficiency, 2023)
Construction is a sector of the economy that directly affects the ecology, changing existing ecosystems and creating a new modified environment, which leads to the transformation of the existing one. Taking into account the importance that the implementation of construction projects has for the successful transformation of the environment, the study of factors of influence, design and other activities of construction participants on the environment, the development of systems for assessing such effects and their implementation in practical activities remains an extremely urgent task. The article examines the regulatory and legal documents of the EU regarding the regulation of the ecological consequences of the impact of construction on the environment, and also systematizes the directions of the impact of construction on the environment. Construction has a significant negative impact on the environment, which is accompanied by the transformation of ecosystems, fragmentation of landscapes, during drilling and blasting, construction of pits and trenches, felling of forests and bushes, pollution of the atmosphere, territories and water areas adjacent to the construction, and noise pollution, damage to the soil layer and washing away pollution from the construction site, the formation of construction waste dumps, etc. That is why the planning, construction and operation of construction sites must be carried out in accordance with environmental standards, and the standards themselves should ensure the minimization of the impact of networks on the environment. Therefore, it is important to improve the existing methods of assessing environmental risks, to form criteria and an assessment mechanism, as well as to bring the Ukrainian legislative and regulatory framework closer to the European one. The features and differences of the preparation of the following documents are determined: Strategic Environmental Assessment (SEA), Environmental Impact Assessment (EIA), Environmental Impact Assessment (EIA), as well as the advantages of using environmental product declarations (EPD) used in the EU in construction as a means of communicating transparent and standardized information about the environmental performance of products, are based on life cycle assessment (LCA) and comply with standards such as ISO 14025. By implementing mandatory and voluntary environmental standards and green building practices, enterprises in the construction sector will be able to play a key role in reducing the impact on the environment environment.